2011
DOI: 10.1111/j.1365-2125.2011.04000.x
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetic–pharmacodynamic analysis for sugammadex‐mediated reversal of rocuronium‐induced neuromuscular blockade

Abstract: WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT• Pharmacokinetics and pharmacodynamics of rocuronium are well known.• A mechanistical pharmacokineticpharmacodynamic model based on limited data describing rocuronium and sugammadex pharmacokinetics has been published.• However, the available pharmacokineticpharmacodynamic model for the effects of sugammadex on rocuronium-induced neuromuscular blockade has limited predictive power. WHAT THIS STUDY ADDS• A pharmacokinetic-pharmacodynamic model is described for rocuronium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 47 publications
3
51
0
Order By: Relevance
“…16 In a first step, sugammadex captures free rocuronium, leading to release of rocuronium from cell receptors; the released blocking agent is then bound to sugammadex. Even though the pharmacokinetic profile of sugammadex is affected by age and renal function, 24 quick reversal (less than 2 min) occurs in lean patients after a sugammadex dose of 2 mg/kg (moderate blockade) or 4 mg/kg (deep blockade), either with propofol or sevofluorane for anesthesia maintainance 24 -26 ; increasing the dose does not hasten recovery, and an effect plateau is seen in most patients around 2 min. 24 -26 However, outliers and slow responders have been detected when sugammadex is administered after a moderate and deep blockades.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 In a first step, sugammadex captures free rocuronium, leading to release of rocuronium from cell receptors; the released blocking agent is then bound to sugammadex. Even though the pharmacokinetic profile of sugammadex is affected by age and renal function, 24 quick reversal (less than 2 min) occurs in lean patients after a sugammadex dose of 2 mg/kg (moderate blockade) or 4 mg/kg (deep blockade), either with propofol or sevofluorane for anesthesia maintainance 24 -26 ; increasing the dose does not hasten recovery, and an effect plateau is seen in most patients around 2 min. 24 -26 However, outliers and slow responders have been detected when sugammadex is administered after a moderate and deep blockades.…”
Section: Discussionmentioning
confidence: 99%
“…24 -26 However, outliers and slow responders have been detected when sugammadex is administered after a moderate and deep blockades. 17,18,24,25 This issue, the presence of outliers, is of concern because it is related to potentially serious complications. Even after a TOFR of 0.9 or more has been achieved, upper airway weakness and an obstructive pattern have been observed in outlier patients.…”
Section: Discussionmentioning
confidence: 99%
“…12 Pharmacokinetic models for rocuronium and sugammadex accounted for age and used allometric scaling to account for size in model parameter predictions. Predictions of effect-site concentrations and drug effect for succinylcholine were made with published pharmacokinetic and pharmacodynamic models.…”
Section: Simulations Of Neuromuscular Blockade and Reversal With Sugamentioning
confidence: 99%
“…As an example, it was observed that after IV bolus administration (10 mg kg The b-CD steady-state volume of distribution (V dss ) and most of its derivatives in all animal species tested correspond well with the respective extracellular fluid volume (Table 7). Thus, it can be concluded that, after IV administration, CDs distribute mainly in the extracellular compartments without involving the deep compartments or storage pools (Kleijn et al 2011). Methylated b-CD has a larger V dss and longer t ½ compared to other CD derivatives which may be due to its ability to interact with cellular membranes and its hemolytic activity (Thompson 1997).…”
mentioning
confidence: 97%